Characteristics of trace metals and phosphorus in seawaters offshore the Yangtze River. Issue 2 (30th November 2017) - Su, Han; Yang, Rujun; Zhang, Aibin; Li, Yan; Qu, Shenglu; Wang, Xuchen
Abstract: This study presents the spatial distribution of total dissolved Cu, Zn, Co, and V during an autumn survey in the East China Sea (ECS). Dissolved Fe and its organic complexation were also investigated. The present study aimed to evaluate the relationship between Cu, Zn, Co, V, D-Fe and its organic ligands and total dissolved phosphate (TDP) in the coastal waters of the ECS. A correlation analysis shows that Cu, Zn and D-Fe were nutrient-like metals, whereas Co and V were non-nutrient-like metals. A multivariate statistical analysis showed that TDP was associated with D-Fe, Cu, Zn and Co, but was not associated with V. Furthermore, TDP was observed to be positively related with D-Fe, while negatively with Fe′, which indicated that the limitation of TDP decreased the uptake of Fe′. This paper improves our understanding of the association among trace metals, TDP and phytoplankton biomass in the ECS. Highlights: Dissolved Fe, Zn, Cu and Co were correlated with phosphorus. V was distinguished from the other trace metals.